Challenges and Opportunities of Sharia Marketing in Indonesia: An Ethical and Cultural Perspective - Nelis Jamjam Munawaroh; Melani; Kurniawan; Hakiki, Muhamad Fuji; Athoillah, Mohamad Anton (ITB AAS INDONESIA Surakarta, 2025)
Sharia marketing in Indonesia holds great potential due to the country's predominant Muslim population. Fundamental sharia principles such as the prohibitions on riba, gharar, and maysir form the foundation for developing marketing practices that align with Islamic teachings. However, the implementation of sharia marketing in Indonesia faces several challenges, including varied consumer understanding of the halal concept, cultural diversity, and competition from more affordable conventional products. Regulations and sanctions from the Indonesian Halal Product Assurance Agency (BPJPH) reinforce business compliance with halal standards, while digital technology provides opportunities for companies to expand consumer education and enhance product transparency. Collaborations with Muslim influencers and the use of social media have also proven effective in raising consumer awareness, especially among younger generations. This study aims to analyze the challenges and opportunities of sharia marketing in Indonesia from an ethical and cultural perspective, as well as identify marketing strategies that can enhance Muslim consumer trust and loyalty. The findings indicate that effective sharia marketing can strengthen the national economy by increasing the competitiveness of halal products, supporting MSMEs, and contributing to the sustainable growth of the halal industry.